Philosophical Dimensions in Mathematics Education
XII, 242 p.
Keywords: Philosophical Dimensions in Mathematics Education brings together diverse recent developments exploring philosophy of mathematics in education. The unique combination of ethnomathematics, philosophy, history, education, statistics and mathematics offers a variety of different perspectives from which existing boundaries in mathematics education can be extended. The ten chapters in Philosophical Dimensions in Mathematics Education offer a balance between philosophy of and philosophy in mathematics education. Attention is paid to the implementation of a philosophy of mathematics within the mathematics curriculum to become a philosophy in mathematics education. In doing so, many chapters provide ideas for actual practice and some practical examples directly usable in teacher training and in mathematics classrooms. Philosophical Dimensions in Mathematics Education is intended for researchers in mathematics education, as well as for those working in the discipline of the philosophy of mathematics. It is also intended for those mathematics and statistics educators who want to broaden their view on mathematics/statistics education. .